PENGARUH PERSEPSI PRODUK UNGGULAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN POLIKLINIK BEDAH DI RSI PKU MUHAMMADIYAH PEKAJANGAN - Susanto Susanto; Rikhlatul Iffah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
The Islamic Hospital PKU Muhammadiyah Pekajangan is a type C private hospital that is growing in Pekalongan. The successful hospital in the future are hospitals that have a competitive power. To win the competition the hospital must provide value and satisfaction to customers or patients through quality of products or services with competitive costs. The Islamic Hospital PKU Muhammadiyah Pekajangan already has a competitive product that is surgical oncology, surgical urology, neurosurgery. In addition The Islamic Hospital PKU Muhammadiyah Pekajangan should be able to know the quality of services provided and understand the interests and patients behavior to use the hospital services if needed health services at the next time. To know the influence of competitive product perception to patient loyalty in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan, and determine the influence of services quality perceptions to patient loyalty in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan, as well as investigate the influence of competitive product and services quality perception together against patient loyalty in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan. The study was quantitative research with cross sectional design. The study was conducted on May-June 2011 in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan. The population was all patients who had used services in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan. The number of samples was 100 respondents. The sampling design was purposive sampling. Data was analyzed used descriptive and inferential statistics with multiple linear regression. The research result showed that competitive products perception influenced patient loyalty (Sig. 0.005 <0.05), and services quality perception influenced patient loyalty (Sig. 0.000 <0.05), as well as competitive products and services quality jointly influenced patient loyalty in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan (Sig. 0.000 <0.05). The perception of competitive products and services quality perception which consists of communication, tangibles, empathy of nursing staff, assurance, responsiveness of the administrative staff, security, responsiveness physician either partially or jointly influence patient loyalty in The Surgical Clinic of Islamic Hospital PKU Muhammadiyah Pekajangan.